ABOUT THE MEAN WIDTH OF SIMPLICES - BÖRÖCZKY jr., K. (Periodica Polytechnica Mechanical Engineering, 1992)
We are interested in the maximal mean width of simplices in Ed having edge-length at most one. Probably the maximum is provided by the regular simplex with edge-length one. We prove it for d ≤ 5 and support this conjecture with some additional arguments.